2018
DOI: 10.1017/s1460396918000274
|View full text |Cite
|
Sign up to set email alerts
|

Compassion satisfaction and fatigue: an investigation into levels being reported by radiotherapy students

Abstract: IntroductionStudies have investigated the prevalence of compassion satisfaction and compassion fatigue in various healthcare professions. However, the majority of evidence is linked to the nursing profession and little is known about paramedical professions such as radiography and even less is known about its prevalence in students. The purpose of this study was to describe the levels of compassion satisfaction and compassion fatigue in the student population and how they varied in time.MethodsStudents underta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
2
3
0
1
Order By: Relevance
“…Inverse relationships of CS with CF measures of STS and BO were consistent with the published literature in undergraduate pre-licensure students (Flinton et al, 2018;Mason & Nel, 2012). Although the inverse relationship of CS and STS was not statistically significant in the current study; these findings were akin to those by McArthur et al (2017) in a sample of Australian veterinary medicine students.…”
Section: Dependent Variable Inter-relationshipssupporting
confidence: 89%
See 1 more Smart Citation
“…Inverse relationships of CS with CF measures of STS and BO were consistent with the published literature in undergraduate pre-licensure students (Flinton et al, 2018;Mason & Nel, 2012). Although the inverse relationship of CS and STS was not statistically significant in the current study; these findings were akin to those by McArthur et al (2017) in a sample of Australian veterinary medicine students.…”
Section: Dependent Variable Inter-relationshipssupporting
confidence: 89%
“…This negative or pessimistic perspective is reflective of those who scored lower on the core self-evaluation measure. These findings support that negative affectivity or neuroticism are significant predictors of BO ( Flinton et al., 2018 ; Škodová et al., 2013 ). Among university students with Type D Personality (prone to negative emotion or a pessimistic affect), Williams and Wingate (2012) found that social support and emotion-focused coping can decrease perceived stress.…”
Section: Discussionsupporting
confidence: 74%
“…En concordancia con el estudio de Yu et al (11) , profesionales con cierta inestabilidad emocional, reactivos a las circunstancias externas y con dificultades para autorregularse emocionalmente después de experiencias de impacto importante como puede ser el sufrimiento y la muerte de las personas a las que asisten, serán las más propensas a desarrollar FC/ETS. Una atención centrada en dicho sufrimiento y la preocupación por su propia posible ineficacia en las labores de acompañamiento, junto con las dificultades para dotar de significado intelectual al sufrir y al proceso de morir sin la cobertura del convencionalismo, fomentarán que el equipo de Enfermería de oncología subraye los aspectos emocionalmente más negativos de una profesión centrada en las personas, en concordancia con las conclusiones de Flinton (27) .…”
Section: Discussionunclassified
“…Exposure to CF and associated conditions is not limited only to oncology nurses and doctors but involves other allied healthcare professionals, such as radiotherapists, psychologists and social workers, among others [ 16 , 17 ]. These healthcare professionals are also involved in the daily care of cancer patients and thus are OHPs [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%